1997
DOI: 10.1023/a:1006809522931
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cryptococcocal meningoencephalitis is always considered secondary to initial lung infection. Because of the unquestionable evidence of haematogenious spread from the lungs, few publications have reported about other possible primary sites of infection or other routes to the central nervous system. This study was designed to investigate the infiltrative pattern of C. neoformans in immunocompromised mice by treatment with dexamethasone. The infection was performed by nasal instillation (30 mice) or injection int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…We also note that veterinary observations in naturally exposed animals ( 45 , 46 ) show fungal cells posterior (deep) into the upper airways, consistent with our observations in intranasally instilled animals. Similarly, penetration of nasal mucosa after intranasal instillation was reported before ( 44 ), demonstrating cryptococci have the capacity to overcome the first defensive layers in respiratory and olfactory mucosa and posits a tropism for the olfactory mucosa due to an unknown factor in this tissue. There are some anatomical differences between turbinates of animals and humans, a topic which was expertly reviewed by reference 51 ; immunological and/or tissue differences are the poorly characterized ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We also note that veterinary observations in naturally exposed animals ( 45 , 46 ) show fungal cells posterior (deep) into the upper airways, consistent with our observations in intranasally instilled animals. Similarly, penetration of nasal mucosa after intranasal instillation was reported before ( 44 ), demonstrating cryptococci have the capacity to overcome the first defensive layers in respiratory and olfactory mucosa and posits a tropism for the olfactory mucosa due to an unknown factor in this tissue. There are some anatomical differences between turbinates of animals and humans, a topic which was expertly reviewed by reference 51 ; immunological and/or tissue differences are the poorly characterized ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 72%
“…While we and others had previously detected cryptococci in upper airways of mice ( 42 44 ), we report for the first time that titan cells are abundant in airway turbinates of mice. Titan cells had been previously observed in nasal cavities of mammals with advanced symptomatic disease: from the necropsied fungal nasal mass of a dog with central nervous system (CNS) disease ( 45 ) and biopsy of nasal granuloma in a cat with localized disease ( 46 ).…”
Section: Discussionsupporting
confidence: 49%
“…In the case of C. neoformans, the possibility of brain dissemination through the nose was investigated previously (35). In mice, yeast cells were observed along the olfactory nerve and the meninges starting at day 3 after intranasal instillation (35).…”
Section: Discussionmentioning
confidence: 99%
“…neoformans, the possibility of brain dissemination through the nose was investigated previously (35). In mice, yeast cells were observed along the olfactory nerve and the meninges starting at day 3 after intranasal instillation (35). Our study differed from that previous study in that we focused on the earliest stages of infection and found no evidence of an upward movement that would result in invasion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…These findings prompted investigations into the possibility of an alternative direct route of CNS entry from the nose. Gomes et al followed the progression of intranasal C. neoformans infection in immunodeficient mice and demonstrated colonization of the olfactory mucosa, invasion along the olfactory nerve, and meningeal involvement (401). In a study of the pathological features of three patients with AIDS and cryptococcal meningitis, C. neoformans was observed in the subarachnoid space around the olfactory tracts and bulbs and in the olfactory nerve fascicles (402).…”
Section: Yeasts and Fungimentioning
confidence: 99%